Compact Polygonal Active-Mirror Laser With Composite Nd:YAG/YAG Gain Medium - Yanzhong Chen; Ye Lang; Lifen Liao; Zhongwei Fan; Jianguo He; Guangyan Guo; Weiran Lin; Yunfeng Ma; Hongbo Zhang; Jian Zhang (IEEE Photonics Journal)
A compact polygonal active-mirror (PAM) laser with composite Nd: YAG/YAG multithin-disk gain medium has been demonstrated with total internal reflection scheme. Five Nd:YAG thin disks with a neodymium concentration of 0.7 at.% and thickness of ∼0.2 mm were bonded to five different surfaces of a hexagonal YAG substrate. With no heat sink, output power of 1.03 W at 1064 nm and beam quality of M2 = 1.21 was obtained from a short-cavity oscillator based on the PAM architecture, under an absorption pump power of 2.30 W, with a slope efficiency and optical to optical efficiency of 55.8% and 44.8%, respectively.